(untitled) (Boletin Médico de Postgrado, 2018)
The hearing loss sometimes occurs in newborns because of family history or other hereditary health problems. Certain situations are related to a child can develop a hearing loss as some infections or medications during pregnancy. The aim of this study was to evaluate the early detection of hearing loss in newborn product of high-risk pregnancy consultation service foniatría decentralized Children’s Hospital Dr. Agustín Zubillaga Barquisimeto Lara State. The study was descriptive, field, no experimental and cross-sectional. The population consisted of 67 infants who were treated in that hospital. Demographics first and second interrogation and otoacoustic emissions results: the technique of direct observation and a registration structured in two parts was used for data collection. It was determined that prematurity is at 71.7% and 16.4% jaundice these being the most predominant and perinatal asphyxia (4%) was not statistically significant, given these results more frequently in females. It is concluded that as much of the sample was represented by newly born pre term and could be controlled by informing pregnant women about early detection of hearing loss in healthy newborns on risk factors that chance this pathology and diagnosis and early intervention.